Analgesia for neuropathic pain by dorsal root ganglion transplantation of genetically engineered mesenchymal stem cells: initial results - Yu, Hongwei (Mol Pain, 2015)
BACKGROUND: Cell-based therapy may hold promise for treatment of chronic pain. Mesenchymal stem cells (MSCs) are readily available and robust, and their secretion of therapeutic peptides can be enhanced by genetically engineering. We explored the analgesic potential of transplanting bone marrow-derived MSCs that have been transduced with lentivectors. To optimize efficacy and safety, primary sensory neurons were targeted by MSC injection into the dorsal root ganglia (DRGs). RESULTS: MSCs were transduced using lentivectors to express enhanced green fluorescent protein (EGFP) or to co-express the analgesic peptide glial cell line-derived neurotrophic factor (GDNF) and EGFP by a viral 2A bicistronic transgene cassette. Engineered MSCs were injected into the 4(th) lumbar (L4) and L5 DRGs of adult allogeneic rats to evaluate survival in the DRGs. MSCs were detected by immunofluorescence staining up to 2–3 weeks after injection, distributed in the extracellular matrix space without disrupting satellite glial cell apposition to sensory neurons, suggesting well-tolerated integration of engrafted MSCs into DRG tissue. To examine their potential for inhibiting development of neuropathic pain, MSCs were injected into the L4 and L5 DRGs ipsilateral to a spinal nerve ligation injury. Animals injected with GDNF-engineered MSCs showed moderate but significant reduction in mechanical allodynia and hyperalgesia compared to controls implanted with MSCs expressing EGFP alone. We also observed diminished long-term survival of allografted MSCs at 3 weeks, and the development of a highly-proliferating population of MSCs in 12% of DRGs after transplantation. CONCLUSIONS: These data indicate that genetically modified MSCs secreting analgesic peptides could potentially be developed as a novel DRG-targeted cell therapy for treating neuropathic pain. However, further work is needed to address the challenges of MSC survival and excess proliferation, possibly with trials of autologous MSCs, evaluation of clonally selected populations of MSCs, and investigation of regulation of MSC proliferation.